Microbiota-Derived Short-Chain Fatty Acids Modulate Expression of Campylobacter jejuni Determinants Required for Commensalism and Virulence - Paul M. Luethy (American Society for Microbiology, 2017)
ABSTRACT Campylobacter jejuni promotes commensalism in the intestinal tracts of avian hosts and diarrheal disease in humans, yet components of intestinal environments recognized as spatial cues specific for different intestinal regions by the bacterium to initiate interactions in either host are mostly unknown. By analyzing a C. jejuni acetogenesis mutant defective in converting acetyl coenzyme A (Ac-CoA) to acetate and commensal colonization of young chicks, we discovered evidence for in vivo microbiota-derived short-chain fatty acids (SCFAs) and organic acids as cues recognized by C. jejuni that modulate expression of determinants required for commensalism. We identified a set of C. jejuni genes encoding catabolic enzymes and transport systems for amino acids required for in vivo growth whose expression was modulated by SCFAs. Transcription of these genes was reduced in the acetogenesis mutant but was restored upon supplementation with physiological concentrations of the SCFAs acetate and butyrate present in the lower intestinal tracts of avian and human hosts. Conversely, the organic acid lactate, which is abundant in the upper intestinal tract where C. jejuni colonizes less efficiently, reduced expression of these genes. We propose that microbiota-generated SCFAs and lactate are cues for C. jejuni to discriminate between different intestinal regions. Spatial gradients of these metabolites likely allow C. jejuni to locate preferred niches in the lower intestinal tract and induce expression of factors required for intestinal growth and commensal colonization. Our findings provide insights into the types of cues C. jejuni monitors in the avian host for commensalism and likely in humans to promote diarrheal disease. IMPORTANCE Campylobacter jejuni is a commensal of the intestinal tracts of avian species and other animals and a leading cause of diarrheal disease in humans. The types of cues sensed by C. jejuni to influence responses to promote commensalism or infection are largely lacking. By analyzing a C. jejuni acetogenesis mutant, we discovered a set of genes whose expression is modulated by lactate and short-chain fatty acids produced by the microbiota in the intestinal tract. These genes include those encoding catabolic enzymes and transport systems for amino acids that are required by C. jejuni for in vivo growth and intestinal colonization. We propose that gradients of these microbiota-generated metabolites are cues for spatial discrimination between areas of the intestines so that the bacterium can locate niches in the lower intestinal tract for optimal growth for commensalism in avian species and possibly infection of human hosts leading to diarrheal disease.